What we measure … and what we should measure in medical education. Issue 1 (14th September 2018) - Boulet, John R; Durning, Steven J
Abstract : Context: As the practice of medicine evolves, the knowledge, skills and attitudes required to provide patient care will continue to change. These competency‐based changes will necessitate the restructuring of assessment systems. High‐quality assessment programmes are needed to fulfil health professions education's contract with society. Objectives: We discuss several issues that are important to consider when developing assessments in health professions education. We organise the discussion along the continuum of medical education, outlining the tension between what has been deemed important to measure and what should be measured. We also attempt to alleviate some of the apprehension associated with measuring evolving competencies by discussing how emerging technologies, including simulation and artificial intelligence, can play a role. Methods: We focus our thoughts on the assessment of competencies that, at least historically, have been difficult to measure. We highlight several assessment challenges, discuss some of the important issues concerning the validity of assessment scores, and argue that medical educators must do a better job of justifying their use of specific assessment strategies. Discussion: As in most professions, there are clear tensions in medicine in relation to what should be assessed, who should be responsible for administering assessment content, and how much evidence should be gathered to support the evaluation process. Although there have been advances in assessment practices, there is still room for improvement. From the student's, resident's and practising physician's perspectives, assessments need to be relevant. Knowledge is certainly required, but there are other qualities and attributes that are important, and perhaps far more important. Research efforts spent now on delineating what makes a good physician, and on aligning new and upcoming assessment tools with the relevant competencies, will ensure that assessment practices, whether aimed at establishing competence or at fostering learning, are effective with respect to their primary goal: to produce qualified physicians. Abstract : What are we assessing and what should we be assessing? This paper explores an ongoing tension regarding which competencies are required for patient care and which are known to be assessable in an effective and efficient manner.